Peak friction angle estimation from joint roughness coefficient of discontinuities of limestone in Peninsular Malaysia - Ailie Sofyiana Serasa,; Goh, Thian Lai; Abdul Ghani Rafek,; Azimah Hussin,; Lee, Khai Ern; Tuan Rusli Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The peak friction angle (φpeak) roughness of discontinuity surfaces is a value that is fundamental to the understanding of shear strength of geological discontinuities, considering its importance in determining the mechanical properties of the discontinuity surface. It is however, both time and cost demanding to determine the peak friction angle as it requires an extensive series of laboratory tests. This paper presents an approach in the form of an experimentally determined polynomial equation to estimate peak friction angle of limestone discontinuity surfaces by measuring the Joint Roughness Coefficient (JRC) values in a field survey study, and applying the fore mentioned empirical correlation. A total of 1967 tilt tests and JRC measurements were conducted in the laboratory to determine the peak friction angles of rough limestone discontinuity surfaces. The experimental results were analyzed and correlated to establish a polynomial equation of φpeak = -0.0635JRC2 + 3.95JRC + 25.2 with coefficient of determination (R2) of 0.99. The laboratory results were also compared with theoretical results calculated from Barton’s linear equation. The results shown that estimation of peak friction angles were more accurate using the newly proposed polynomial equation since the percentage differences between measured and calculated peak friction angles is less than 6% compared to estimation from Barton’s linear equation where the percentage of differences is less than 11%. The proposed correlation offers a practical method for estimation of peak friction angles of discontinuity surfaces of limestone from measurement of JRC in the field.